Design of tailored oxide-carbide coating on carbon fibers for a robust copper/carbon interphase. (March 2020) - Constantin, Loic; Fan, Lisha; Zou, Qiming; Thomas, Benjamin; Roger, Jérôme; Heintz, Jean-Marc; Debiemme-Chouvy, Catherine; Mortainge, Bruno; Lu, Yong Feng; Silvain, Jean-Francois
Abstract: The lack of robust interphases between carbon and most metals prevent the exploration of the full scope potential of carbon-based metal matrix composites. Here, we demonstrated a scalable and straightforward way to produce strong interphase between copper (Cu) and carbon fibers (CFs) by designing a tailored titanium oxide-carbide coating (TiOy -TiCx ) on CFs in a molten salt process. The oxide-carbide composition in the graded layer strongly depends on the coating temperature (800–950 °C). A coating with a high TiOy content obtained at a low coating temperature (800 °C) contributes to better molten-Cu wetting and strong adhesion energy between CFs and Cu during a subsequent exposure at 1200 °C. The Cu wetting angle for the TiOy -TiCx -CF sample obtained at 800 °C was ∼80° ± 5° with a Cu surface coverage of ∼50% versus ∼115° and ∼10% for the TiCx -CF sample made at 950 °C. The kinetic analysis of the coating process step by step suggests a growth rate limited by the mass-transfer through the coated layer. This method provides a novel approach to improve the thermal conductivity of Cu/C composite for thermal management applications. Graphical abstract: Image 1